Front Cover: Precision Glycodendrimers for DC‐SIGN Targeting (Eur. J. Org. Chem. 29/2022). Issue 29 (26th July 2022) - Goti, Giulio; Colombo, Cinzia; Achilli, Silvia; Vivès, Corinne; Thépaut, Michel; Luczkowiak, Joanna; Labiod, Nuria; Delgado, Rafael; Fieschi, Franck; Bernardi, Anna
Abstract : The Front Cover shows a blueprint for the design of a multivalent ligand of the C‐type lectin receptor DC‐SIGN. The compound features a tetravalent rigid scaffold that enables for the multivalent presentation of glycomimetics in a spatially defined fashion. This molecular architecture achieves strong binding avidity towards DC‐SIGN and increased selectivity over the C‐type lectin langerin, which is characterized by a distinct spatial arrangement of the carbohydrate recognition domains. Cover design by Mr. Francesco Frullini. More information can be found in the Research Article by F. Fieschi, A. Bernardi et al .